Earthworms of the 'acaecate' Pheretima group in Vietnam (Oligochaeta: Megascolecidae), with description of a new species from the Mekong delta - Nguyen, Tung T.; Tran, Binh T.t.; Nguyen, Anh D. (Zootaxa, 2014)
The 'acaecate' Pheretima group from Vietnam is revised, with description of a new species, Polypheretima mekongmontis sp. nov. A total of 18 species of three genera, Metapheretima Michaelsen, 1928, Planapheretima Michaelsen, 1934, and Polypheretima Michaelsen, 1934 has been recorded from Vietnam. Caecate species of Planapheretima are included here as well. Planapheretima arboricola (Rosa, 1890), Pl. lacertina (Chen, 1946), Pl. tenebrica (Chen, 1946), Polypheretima elongata (Perrier, 1872), and Po. taprobanae (Beddard, 1892) are originally recorded from other countries; all remaining species are native to Vietnam. The species Polypheretima tani (Thai, 1996) and Po. tiencanhensis (Pham, 1995) are transferred to the genus Metapheretima. A key to species and distribution maps are also presented.